Potensi dan Persepsi Pengunjung Terhadap Museum Kayu di Sampit - Cakra Birawa; Renhart Jemi; M. Yusdianor; Ahmad Fahmi; Abung Abung (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2023)
The Wood Museum in the city of Sampit was built as a place to store historical objects to commemorate the glory of East Kotawaringin Regency in the wood industry. The existence of this wooden museum is very important considering that the museum does not only have a function as a protector of cultural heritage objects, but also as a place for forming ideology, discipline and developing knowledge for the public. This study aims to determine the potential and perceptions of visitors to the wood museum. The research method is in the form of observation and structured interviews using a questionnaire, then the data is analyzed by referring to the Museum Standard Guidelines (Ministry of Education and Culture, 2020) and SNI 9042:2021. The results of the study showed a) The potential for the Wood Museum in the city of Sampit was classified as Adequate (value 2.22). This potential is supported by accessibility and supporting facilities with a Sufficient value (2.95). b) The people of Sampit City are very aware of the existence of the Wood Museum, but several program activities have not been implemented causing a lack of community visits to the Wood Museum.